Fish Species Diversity From Someșul Cald River: 50Years After Cascade Dam Constructions - Lațiu, Călin; Papuc, Tudor; Muntean, George; Uiuiu, Paul; Constantinescu, Radu; Matei-Lațiu, Maria-Cătălina; Nicula, Alexandru-Sabin; Craioveanu, Cristina; Mireșan, Vioara; Cocan, Daniel (Frontiers in Environmental Science, 2022)
In the present study, changes caused by cascade dam construction in fish species composition, distribution, and diversity were analyzed on Someșul Cald River, Romania. Cascade dam constructions may act as a freshwater stressor both on short and long term. The river was divided into two sections according to the positioning of the cascade dams (T1-inferior section, respectively T2-superior section). In the T1 section, 8 sampling stations were established while in the T2 section 12 sampling stations were established. A total number of 1789 specimens grouped in 12 species and 8 families were sampled from August to September 2018. The most abundant species in both sections was S. trutta. The most abundant family was Salmonidae with 66.2%. Alpha diversity (species richness) in the T2 section was higher than in T1 (T2=12 species vs. T1=9 species). The Kruskal-Wallis test indicated no significant differences (p>0.05) in the case of beta diversity of T1 vs. T2 (Sørensen coefficient). The species that contributed most to the dissimilarities between the two river sections were T. thymallus, B. carpathicus, C. gobio, and S. cephalus, their summed contribution to the dissimilarity being larger than 50%. The analyzed environmental variables influenced the distribution of some fish species. Alpha and beta diversity distribution on elevation gradient showed that stations close to reservoirs had more species (both in T1 and T2 sections) than the other stations, clearly showing that the distance from lake/reservoir is influencing species richness. The effect of dams from Someșul Cald River on fish species distribution was analyzed by comparing previous data (before 1968) to recent collected data.